Surgeons’ opinions and concerns regarding prophylactic mesh placement when conducting a permanent ileo- and colostomy A survey among 172 surgeons in Germany, Switzerland, and Austria - Paasch, Christoph; Kalmykov, Egan Leonidovich; Lorenz, Ralph; Neveling, Nele; Mantke, Rene (Frontiers in Surgery, 2024)
BackgroundProphylactic mesh placement when creating a permanent colostomy was recommended by the 2017 European Hernia Society guidelines on the prevention and treatment of parastomal hernias (GPTPH2017). The extent of this recommendation is under debate based on the long-term data from clinical trials. Our aim was to conduct a survey of surgeons revealing perspectives and concerns regarding GPTPH2017 and to discuss their concerns.MethodsFrom January 2023 to September 2023 a survey among surgeons of Germany, Switzerland and Austria was conducted. The questionnaire addressed demographic data of the participants, information on work experience/location, number of elective permanent colo- and ileostomies, and opinions on the recommendation of GPTPH2017 for prophylactic mesh placement.ResultsA total of 172 surgeons from Germany, Austria and Switzerland answered the questionnaire and 59 of them stated professional experience of 20–30 years. Most of the surgeons (n = 51, 31.3%) worked in a primary care hospital. A total of 112 participants were familiar with the GPTPH2017. Sixty-five surgeons (40%) stated that they never conduct a prophylactic mesh placement when creating an elective permanent colostomy (rarely, n = 44 (26.7%). Seven participants always place a mesh (4.2%, missing data: 7). Main concerns regarding prophylactic mesh placement was the concern of surgeons about wound infection (n = 107, 67.7%) and lack of evidence (n = 65, 41.1%). For some participants the GPTPH2017 is seen to be industry-driven with low evidence, too old and leading to overtreatment.ConclusionsThe main reason for not placing a prophylactic mesh when conducting a permanent colostomy was the risk of wound infection.